2009 Data Compression Conference 2009
DOI: 10.1109/dcc.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

Analog Joint Source Channel Coding Using Space-Filling Curves and MMSE Decoding

Abstract: We investigate the performance of a discrete-time all-analog-processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Three values of k, k = 1, k = 2 and k = 4, are considered, and the applied non-linear mappings are the standard 2:1 and 4:1 space-filling curves in (2) and (3), respectively, plus the circular approximation. By applying the parameter optimization method proposed in [11], ∆ and α are jointly optimized for each channel signalto-noise ratio (CSNR), and optimal energy allocation is performed for each band. In order to reduce the optimization complexity, in all results presented here ML rather than MMSE is considered, which leads to some performance loss.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three values of k, k = 1, k = 2 and k = 4, are considered, and the applied non-linear mappings are the standard 2:1 and 4:1 space-filling curves in (2) and (3), respectively, plus the circular approximation. By applying the parameter optimization method proposed in [11], ∆ and α are jointly optimized for each channel signalto-noise ratio (CSNR), and optimal energy allocation is performed for each band. In order to reduce the optimization complexity, in all results presented here ML rather than MMSE is considered, which leads to some performance loss.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Moreover, since no long blocks are used the delay is very small. We have recently shown that, by properly optimizing the curve parameters, the use of MMSE decoding for Gaussian and Laplacian sources transmitted over AWGN channels results in a performance that is very close to the theoretical limits in the whole SNR region [11].…”
Section: Ii-b Space-filling Curves As Analog Joint-source Channel Enmentioning
confidence: 95%
See 2 more Smart Citations
“…MMSE decoding has been shown to achieve a substantial performance improvement over ML decoding at low CSNRs under 2:1 bandwidth reduction [10]. For 1:2 bandwidth expansion, the MMSE decoding rule can be written as followŝ…”
Section: A Shannon-kotel'nikov Mappingmentioning
confidence: 99%